Paul, grace and freedom: essays in honour of John K. Riches - Middleton, Paul; Riches, John Kenneth (T & T Clark biblical studies, 2009)
John Riches : an appreciation / John Eldridge -- Pt. 1. Grace and human agency in the New Testament and other writings. Grace within and beyond reason : Philo and Paul in dialogue / John M.G. Barclay -- 'Everything is clean' and 'everything that is not of faith is sin' : the logic of Pauline casuistry in Romans 14.1-15.13 / Troels Engberg-Pedersen -- 'I believe; help my unbelief!' : human faith and divine faithfulness in Mark 9.14-29 / Joel Marcus -- Paul and Matthew on the Torah : theory and practice / David C. Sim -- Testing the boundary : ritual, moral and supramoral responsibility in Jesus and Paul / Karen Wenell -- 'Dying we live' (2 Cor. 6.9) : discipleship and martyrdom in Paul / Paul Middleton -- Pt. 2. Reception and theology. Who is freedom for? : Martin Luther and Alain Badiou on Paul and politics / Stephen Chester -- William Blake and life in the divine body / Christopher Rowland -- Constructing African Christianity : the voice of Paul in the formative teachings of Isaiah Shembe / Gerald West -- 'Your circumcision has become uncircumcision' (Rom 2.25) : context and culture in New Testament study / Leslie Milton -- P.T. Forsyth and the Christian life / Angus Paddison -- Against pecking : Christian law after Pentecost / Ben Quash -- Afterword: Paul, grace and freedom : a response / John Riches